KEHIDUPAN SOSIAL EKONOMI KELUARGA PENAMBANG EMAS DI KENAGARIAN BIDAR ALAM KECAMATAN SANGIR JUJUAN KABUPATEN SOLOK SELATAN - Risyanti, Cici Gusnia; Edial, Helfia; Zahara, Leni (STKIP PGRI Sumbar, 2013)
The gold mining activities in general changing incomes. Increase in income will affect the lives of people both social and economic . This study aims to find , analyze and discuss : 1 ) social life ( social interaction , education and health ) , 2 ) Economic Life ( income and home state ) gold miners in Kanagarian Â Bidar Alam Kecamatan Sangir Jujuan Kabupaten Solok Selatan . This research is a qualitative study using interviews with informants techniques that amount to as many as 19 gold miners in Kanagarian Bidar Alam Kecamatan Sangir Jujuan Kabupaten Solok Selatan.Research results showed : 1 ) social interaction both with each other and with the community of gold miners around the neighborhood are good , the childs education there are gold miners up to college and some are only finished elementary school due to lack of desire to continue to pursue higher education , and gold miners were able to finance his familys health , but tend to use traditional medicine first compared to the health center for treatment , 2 ) Income mining community can not be ascertained , sometimes can only get Rp 200,000 , - and can sometimes reach Rp 3.000.000 , - every time mining for gold , and the condition of the miners has improved , which is usually abandoned houses , now in general is permanent.